Implications of detecting serum monoclonal protein by MASS‐fix following stem cell transplantation in multiple myeloma. (20th November 2020) - Abeykoon, Jithma P.; Murray, David L.; Murray, Isaiah; Jevremovic, Dragan; Otteson, Gregory E.; Dispenzieri, Angela; Arendt, Bonnie K.; Dasari, Surendra; Gertz, Morie; Gonsalves, Wilson I.; Kourelis, Taxiarchis V.; Muchtar, Eli; et al.
Summary: Measurable residual disease (MRD) assessment by marrow‐based next‐generation flow cytometry (NGF) following autologous stem cell transplantation (ASCT) may lead to false‐negative results due to patchy marrow involvement and extramedullary disease in patients with multiple myeloma. We assessed the value of simultaneous MRD evaluation with NGF and serum matrix‐assisted laser desorption ionization time‐of‐flight mass spectrometry (MASS‐FIX). Of all 61 complete responders who were NGF‐negative for MRD, around day‐100 post ASCT, 59% were MASS‐FIX‐positive. At median follow‐up of 26 months, 69% of MASS‐FIX(+)/NGF(−) patients were alive and progression‐free versus 96% of MASS‐FIX(‐)/NGF(−) patients, P  = 0·02. MASS‐FIX, a simple peripheral blood‐based assay complements marrow‐based NGF to accurately prognosticate patients with myeloma.